Location Communication in Leipzig and Thoughts About Destination Management. - Jacke, Christian Albert (Springer, 2018)
The first-hand report of the former Mayor for Economic Affairs, Real-Estates and Tourism of the City of Leipzig and present-day consultant and economic mediator covers the entire range from the beginnings of the reconstruction of the City of Leipzig via its successful repositioning in the 25 years after the German wall came down up to the establishment of a management and marketing concept for the development and institutionalization of rules in the corporate governance principles of the city as an enterprise. The LEIPZIG KOMMT! location campaign and its successor Leipziger Freiheit represent measures which in every aspect were successfully developed and implemented. This article portrays the development of the campaign, outlines the project structure and describes the principle of the marketing management process which has had the effect of creating consensus among the decision-makers of the region.
Keywords: Stadtökonomie; Wirtschaftsentwicklung; Stadtentwicklung; Stadtmarketing; Wirtschaftsstandort; Corporate Governance; Fallbeispiel